2021
DOI: 10.3390/ijerph18042032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Music-Based Rhythmic Auditory Stimulation on Gait and Balance in Subacute Stroke

Abstract: Gait and balance impairments are common after stroke. This study aimed to evaluate the effect of a music-based rhythmic auditory stimulation (RAS) in combination with conventional physiotherapy on gait parameters and walking ability in subacute stroke. This single-blind, historical controlled trial, included 55 patients who had suffered a stroke within the three weeks prior to enrolment. Patients from 2018 (n = 27) were assigned as the historical control group whereas 2019 patients (n = 28) received music-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…However, only six of the eight studies reported clear results of a positive outcome on gait ability from direct application of MST [15][16][17]19,20,22]. The cases conducted by Hayden and Gonzalez-Hoelling et al both reported findings that were unclear and showed no observable distinctions between experimental and control groups [18,21]. The MST interventions implemented to reveal positive outcomes included daily listening, MMF, RAS, and therapy sessions involving physical movement with music in the background or as direct usage [15][16][17]19,20,22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, only six of the eight studies reported clear results of a positive outcome on gait ability from direct application of MST [15][16][17]19,20,22]. The cases conducted by Hayden and Gonzalez-Hoelling et al both reported findings that were unclear and showed no observable distinctions between experimental and control groups [18,21]. The MST interventions implemented to reveal positive outcomes included daily listening, MMF, RAS, and therapy sessions involving physical movement with music in the background or as direct usage [15][16][17]19,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies investigating music therapy in stroke rehabilitation were included in the review, of which four conducted RAS, one conducted MMF, one conducted R-MT, and two conducted more individually defined music interventions [15][16][17][18][19][20][21][22]. The majority of included studies -six of the eight -reported positive outcomes on gait measures among stroke patients who received music or rhythmic therapies [15][16][17]19,20,22].…”
Section: Table 1: Summary Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Music might be used for rehabilitation purposes since it may change the activity of many brain structures (e.g., related to sensory-motor processing, motivation, affect, attention, and memory) and induce plastic changes in some brain networks [5,6]. Additionally, at the neurochemical level, music stimuli influence the function of stress and arousal systems [7].…”
Section: Introductionmentioning
confidence: 99%